Analysis of rainfall pattern by using new weather station in Universiti Malaysia Pahang (UMP), Campus Gambang - Teo, Wei Hui (2014)
The set-up of weather station is inevitable to collect the data in order to identify the rainfall pattern of certain area. The collected data also can be used for research and planning our daily activities. Although there is one weather station existed in Universiti Malaysia Pahang (UMP) Gambang, the location is no longer suitable to collect the weather data. The weather station in UMP Gambang is needed to relocate due to obstructions and developments in vicinity which may affect the accuracy of the data. The set-up of weather station is conducted at UMP Gambang. The ideal criteria and new location that fulfil the requirement to set up a weather station are at Kolej Kediaman 2 UMP Gambang. The ideal location and criteria is determined by refer to maival and standard guidelines. The data from Department of Irrigation and Drainage, Malaysian Meteorological Department and weather station of UMP Pëkan is used for analysed rainfall pattern. The rainfall data collected from the weather station UMP Gambang were also analysed to identifythe effect- of rainfall pattern due to weather change. The relationship between relative humidity, temperature and wind speed towards the rainfall pattern is analysed. When there are increases of temperature, the relative humidity is relatively lower and affects the amount rainfall. Although the relative humidity of the surrounding is very high, it is not necessary having rainfall. Besides that, it is found that the yearly rainfall amount from 2009 to 2013 for surrounding area Gambang shows not consistent for 5 consecutive years. The minimum and maximum total yearly data is 14176.1 mm and 19904 mm at 2010 and 2009 respectively.